The Coexpression of Reelin and Neuronal Nitric Oxide Synthase in a Subpopulation of Dentate Gyrus Neurons Is Downregulated in Heterozygous Reeler Mice - Raquel Romay-Tallón; Iria G. Dopeso-Reyes; April L. Lussier; Lisa E. Kalynchuk; Hector J. Caruncho (Neural Plasticity)
Reelin is an extracellular matrix protein expressed in several interneuron subtypes in the hippocampus and dentate gyrus. Neuronal nitric oxide synthase (nNOS) is also expressed by interneurons in these areas. We investigated whether reelin and nNOS are co-localized in the same population of hippocampal interneurons, and whether this colocalization is altered in the heterozygous reeler mouse. We found colocalization of nNOS in reelin-positive cells in the CA1 stratum radiatum and lacunosum moleculare, the CA3 stratum radiatum, and the dentate gyrus subgranular zone, molecular layer, and hilus. In heterozygous reeler mice, the colocalization of nNOS in reelin-positive cells was significantly decreased only in the subgranular zone and molecular layer. The coexpression of reelin and nNOS in several hippocampal regions suggests that reelin and nNOS may work synergistically to promote glutamatergic function, and the loss of this coexpression in heterozygous reeler mice may underlie some of the behavioral deficits observed in these animals.